Maternal Factors in Neonatal Hypocalcaemia: A Study in Three Ethnic Groups. Issue 5759 (22nd May 1971) - Watney, Patsy J. M.; Chance, G. W.; Scott, P.; Thompson, Joan M.
Abstract : To assess the significance of various maternal and neonatal factors in the aetiology of neonatal tetany we have investigated the serum calcium, phosphorus, magnesium, and heat-labile alkaline phosphatase of 250 mothers from three ethnic groups at several stages of pregnancy and the serum calcium, phosphorus, and magnesium of many of their infants. Subclinical hypocalcaemia was found to be much commoner in full-term infants on the sixth day of life than is generally appreciated, especially during the winter months and in babies of Asian parents. It is considered that this is a result of high phosphorus loads in artificial milks and is also influenced by maternal vitamin D and possibly calcium intake during pregnancy. The importance of ensuring that Asian women take adequate vitamin D supplements during pregnancy is stressed.